THE INFLUENCE OF EMOTIONAL INTELLIGENCE, AFFECTIVE COMMITMENT, AND ORGANIZATIONAL CITIZENSHIP BEHAVIOR ON THE EMPLOYEE PERFORMANCE AT PT CHAKRA NAGA FURNITURE JEPARA - Vivi Noviyanti; Endang Sulistiyani; azizah azizah (Politeknik Negeri Semarang, 2018)
The purpose of this research was to determine the effect of emotional intelligence, affective commitment, and organizational citizenship behavior (OCB) on the employee performance at Chakra Naga Furniture Jepara. This study used a sample of saturated, whereby the entire study population was selected into the sample as many as 50 employees. The data analysis technique used in this study linear analysis techniques with the help of Software Package for Social Science (SPSS) for Windows. It is showed that emotional intelligence, affective commitment, and organizational citizenship behavior (OCB) positive and significant impact on performance. This study shows that the employees that have high intelligence would be optimal in demonstrating their performance. Employees who have a high affective commitment to the organization where his performance will likely increase. This situation is also coupled with employees’s organizational citizenship behavior (OCB) which is high to where he works as well as the other employees will demonstrate improved their performance and attitude that they are likely more sociable, friendly, and more able to accept a job without much complain and denial.